The Feasibility and Effectiveness of Web-Based Advance Care Planning Programs: Scoping Review - van der Smissen, Doris; Overbeek, Anouk; van Dulmen, Sandra; van Gemert-Pijnen, Lisette; van der Heide, Agnes; Rietjens, Judith AC; Korfage, Ida J (JMIR Publications, 2020)
BackgroundAdvance care planning (ACP) is a process with the overall aim to enhance care in concordance with patients' preferences. Key elements of ACP are to enable persons to define goals and preferences for future medical treatment and care, to discuss these with family and health care professionals, and to document and review these if appropriate. ACP is usually conducted through personal conversations between a health care professional, a patient, and-if appropriate-family members. Although Web-based ACP programs have the potential to support patients in ACP, their effectiveness is unknown. ObjectiveThis study aimed to assess the feasibility and effectiveness of Web-based, interactive, and person-centered ACP programs. MethodsWe systematically searched for quantitative and qualitative studies evaluating Web-based, interactive, and person-centered ACP programs in seven databases including EMBASE, Web of Science, Cochrane Central and Google Scholar. Data on the characteristics of the ACP programs' content (using a predefined list of 10 key elements of ACP), feasibility, and effectiveness were extracted using a predesigned form. ResultsOf 3434 titles and abstracts, 27 studies met the inclusion criteria, evaluating 11 Web-based ACP programs-10 were developed in the United States and one in Ireland. Studied populations ranged from healthy adults to patients with serious conditions. Programs typically contained the exploration of goals and values (8 programs), exploration of preferences for treatment and care (11 programs), guidance for communication about these preferences with health care professionals or relatives (10 programs), and the possibility to generate a document in which preferences can be recorded (8 programs). Reportedly, participants were satisfied with the ACP programs (11/11 studies), considering them as easy to use (8/8 studies) and not burdensome (7/8 studies). Designs of 13 studies allowed evaluating the effectiveness of five programs. They showed that ACP programs significantly increased ACP knowledge (8/8 studies), improved communication between patients and their relatives or health care professionals (6/6 studies), increased ACP documentation (6/6 studies), and improved concordance between care as preferred by the patients and the decisions of clinicians and health care representatives (2/3 studies). ConclusionsWeb-based, interactive, and person-centered ACP programs were mainly developed and evaluated in the United States. They contained the key elements of ACP, such as discussing and documenting goals and preferences for future care. As participants considered programs as easy to use and not burdensome, they appeared to be feasible. Among the 13 studies that measured the effectiveness of programs, improvement in ACP knowledge, communication, and documentation was reported. The concordance between preferred and received care is yet understudied. Studies with high-quality study designs in different health care settings are warranted to further establish the feasibility and effectiveness of Web-based ACP programs.